Translation and plurisemiotic practices: Examples of mural painting - Gambier Yves; Juzeleniene Saule; Petroniene Saule (ROEHAMPTON UNIV SCH ARTS, 2022)
Intersemiotic translation as defined by Roman Jakobson (1959) has been referred to and used in many different case studies including text and pictures or sounds. This is also the starting point for our research. We draw as well on the concept of multimodality and sketch the different historical and social functions of murals. The article consists of two research projects. The first project is based on a programme related to citizens' cultural awareness and social inclusion launched by the municipality of Kaunas (Lithuania). We describe all the steps from the written official call to the implementation of their ideas by the artists. Two murals (2016-2018) are under systematic scrutiny. The second project refers to "Places of Interest" (2016), a project combining a photo of a place, a recorded description of the photograph and a painting derived from the recorded description by an artist living in a different country. The murals and the photo/painting are framed within a specific verbal context. We explore how the meanings are translated, how the different agents of the process interpret the directives and narratives. In the last section, we discuss further the conceptual implications of our work, especially the relevance of 'intersemiotic translation' and the need to re-question the concept of 'translation'.